Tracing livelihood trajectories: Patterns of livelihood adaptations in rural communities in eastern Nepal - Lama, Phu Doma; Becker, Per; Bergström, Johan (Geographical Journal of Nepal, 2019)
Mountain communities are adapting their livelihoods to a complex combination of social, political and economic changes and associated risks. Despite recognition of adaption in response to multiple changes in sustainable livelihood and critical climate change literature, risks attributed to biophysical effects of climate change have increasingly assumed importance. Consequently, diversification is promoted as an adaptive approach to reduce such risks. However, understanding livelihood adaptation from the vantage point of climate change alone might lead to a limited understanding of non-climatic factors also shaping it. This paper proposes understanding adaptation through analysing long-term livelihood changes and using society rather than climate change as a conceptual starting point. It argues that such an approach has better potential to highlight a broader range of dynamic drivers operating over decades and to inform contextually grounded rural livelihood adaptation policies. Changes are traced in the overall livelihood trajectories among four rural communities in Nepal, in living memory, to understand the role of adaptation in shaping it. Qualitative life narratives were collected and complemented by key informant interviews, field observations and the analysis of official documents. The findings suggest that livelihoods have shifted not only from subsistence towards income generation but also from engagement in diverse livelihood sectors towards specialisation; the opposite of the advocated diversification. The role of political, economic, social and cultural processes within and outside the community has been prominent in shaping this trajectory.